A new species and two new taxon records of Digitaria (Poaceae: Panicoideae) for Thailand - Boonsuk, Boonchuang; Chantaranothai, Pranom; Hodkinson, Trevor R. (Phytotaxa, 2014)
Field and herbarium studies have revealed a greater diversity of Thai Digitaria (Poaceae) than previously known. A new species, Digitaria thailandica, and two new taxon records, D. setigera var. calliblepharata and D. thyrsoidea, are described and illustrated.